A Germline Mutation in ATR Is Associated With Lung Adenocarcinoma in Asian Patients - Bao, Guangyao; Guan, Xiaojiao; Liang, Jie; Yao, Yao; Xiang, Yifan; Li, Tian; Zhong, Xinwen (Frontiers in Oncology, 2022)
Background: Familial lung cancer (FLC) accounts for 8% of lung adenocarcinoma. It is known that a few germline mutations are associated with risk incresing and may provide new screening and treatment option. The goal of this study is to identify an FLC gene among three members of an FLC family. Methods: To uncover somatic and embryonic mutations linked with familial lung cancer, whole exome sequencing was done on surgical tissues and peripheral blood from three sisters in a family diagnosed with pulmonary lung adenocarcinoma (LUAD). At the same time, single-cell RNA sequencing (scRNA-seq) and bulk RNA sequencing data in public databases were enrolled to identify specific gene expression level. Results: Ataxia Telangiectasia and Rad3-Related Protein (ATR) gene C.7667C >G (p.T2556S) mutation were found in 3 patients with familial lung cancer. Whole-genome sequencing revealed that the three sisters exihibited similar somatic mutation patterns. Besides ATR mutations, common mutated genes (BRCA1, EGFR and ROS1) that characterize LUAD were also found in 5 tumor samples. Analysis for the ATR expression in LUAD patients by single cell sequencing data, we found ATR expression of tumor patiens at high level in immune cells when compared with normal patients, but the expression of ATR in stromal cells has the opposite result. Conclusion: We found a germline mutation in the ATR gene in three sisters of a Chinese famliy affected by familial lung cancer, which may be a genetic factor for lung cancer susceptibility.